Genetic diversity, population structure, and historical demography of a highly vagile and human‐impacted seabird in the Pacific Ocean: The red‐tailed tropicbird, Phaethon rubricauda. Issue 2 (16th September 2020) - Varela, Andrea I.; Brokordt, Katherina; Ismar‐Rebitz, Stefanie M.H.; Gaskin, Chris P.; Carlile, Nicholas; O'Dwyer, Terence; Adams, Josh; VanderWerf, Eric A.; Luna‐Jorquera, Guillermo
Abstract: Many seabird breeding colonies have recovered from heavy anthropogenic disturbance after conservation actions. The widely distributed red‐tailed tropicbird, Phaethon rubricauda, was used as a model species to assess potential anthropogenic impacts on the genetic diversity of breeding colonies in the Pacific Ocean. Cytochrome c oxidase subunit I and control region sequences analyses were conducted across the range of the species in the Pacific Ocean. The study sites were at islands without human‐related disturbance (non‐impacted islands) and with human‐related disturbance (impacted islands). We hypothesized that (i) breeding colonies of the red‐tailed tropicbird on impacted islands have lower genetic diversity compared with colonies on non‐impacted islands, and (ii) breeding colonies of the red‐tailed tropicbird show significant fine and broad‐scale genetic structure across the Pacific Ocean. Bayesian skyline analyses were conducted to infer past changes in population sizes. Genetic diversity was similar between impacted and non‐impacted islands. There was significant broad‐scale genetic structure among colonies separated by over 6, 000 km, but a lack of significant fine‐scale genetic structure within Australasia and Hawai'i, although a significant level of differentiation was found within Chile with ΦST analyses. Skyline analyses showed that effective population sizes remained relatively constant through time, but experienced either a slight decrease or the end of an expansion event through the last 1, 000 years. These changes may be related to the arrival of humans on Pacific islands. Impacted islands may have received immigrants from other relatively close islands, buffering the loss of genetic diversity. However, it is also possible that colonies have retained ancestral variation or that a large effective population size coupled with a long generation time (13 years) has prevented the loss of genetic diversity in human‐impacted islands. Future research using higher‐resolution markers is needed to resolve the population genetic structure of the red‐tailed tropicbird in an ecological time‐scale.